Pengembangan Video Pembelajaran Berbasis Problem Based Learning Pada Materi Bagun Ruang Sisi Datar - Sugandi, Sugandi; Huda, Ummul (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The main problem in this research is the lack of adequate learning media, the textbooks which often display 3D images simplified into 2D, which can cause misunderstanding of students towards the concept of three-dimensional shapes. It also found that students showed high interest in learning using videos due to the limited environment by the latest technology. The purpose of this research is to produce a valid and practical Problem Based Learning (PBL) video. This type of research is development research with the 4-D development model, which consists of four stages. Define is the stage to determine why the product developed, along with its specifications. Design is designing the product based on the predetermined specifications. Develop is to produce the product, testing its validity and practicality to ensure that the outcomes meet the expected specifications. Disseminate is the stage of distributing the validated product to a wider audience for practical use but not used in this research. Data were carried out through questionnaires. The instruments used in this study include validation sheets, teacher response questionnaires, and student response questionnaires. Based on the research results conducted on ninth-grade students of SMP IT An-Nahl, it can be concluded that the PBL-based learning video for flat-sided space shapes material has a high validity level with a percentage of 85.03%. For practicality testing, the teacher response questionnaire showed an average percentage of 87.3%, which is categorized as very practical, while the student response questionnaire obtained an average percentage of 93%, also categorized as very practical.